Costs and Savings Associated With the Police Use of the interRAI Brief Mental Health Screener - Hoffman, Ron; Harman, Jeffrey; Kinsell, Heidi; Brown, Gregory (Frontiers in Psychiatry, 2021)
Background: The police response to mental health calls for service continues to be highly controversial. Strategies to improve the police response include Crisis Intervention Team (CIT) training and various forms of co-response models neither of which have been subjected to comprehensive evaluations, particularly as to cost-efficiency. A new approach is the use of the interRAI Brief Mental Health Screener to enhance police officer ability to identify persons with serious mental disorders. The purpose of the current study is to evaluate the costs and cost efficiency of the police response to mental health calls using the interRAI Brief Mental Health Screener. Method: Secondary data was analyzed from the use of the screener from 2018-2020 by police officers in a mid-sized Canadian city. Changes were measured in the overall number of interactions police officers had with persons with mental health disorders, the number of incidents where police officers referred the person to hospital, and the time officers remained in the emergency department. Results: A total of 6,727 assessments were completed with involuntary referrals decreasing by 30%, and voluntary referrals by 34%. The overall time police officers were involved in involuntary referrals decreased from 123 minutes in 2018 to 113 minutes in 2020. The average emergency department wait time for voluntary referrals dropped from 41 minutes in 2018 to 27 minutes in 2020, while involuntary referrals decreased from 61 minutes in 2018 to 42 minutes in 2020. Each averted involuntary referral to the emergency department resulted in a savings of $81, on average during the study period. Conclusion: An analysis of the costs and costs savings associated with the use of the screener demonstrate that it is a worthwhile investment for police services. An additional benefit is its ability to collect mental health statistics that may be useful to police leaders to justify budgets. Future studies should attempt to devise some method of collecting pre-implementation data that would reveal the true costs and cost-efficiency of using the BMHS, which have been shown to be significant in the current study however, undoubtedly are under-estimated.